IMPLEMENTATION OF MEDICAL INFORMATION RELEASE FOR COMMERCIAL INSURANCE PURPOSES AT RSI SULTAN AGUNG SEMARANG IN 2021 - suyoko suyoko; Novika Gema Palupi; Maulana Tomy Abiyasa; Retno Astuti Setijaningsih (Dian Nuswantoro Semarang, 2022)
ABSTRACTLaw No. 44 of 2009 concerning Hospitals, states that hospitals are obliged to respect and protect the rights of patients. The early survey found that completion time in the implementation of the release of medical information for claims was constrained, depend on the presence and willingness of doctors to fill out medical information. These obstacles can possibly cause the loss for patients. The purpose of this study was to analyze the implementation of the release of medical information for commercial insurance claims at RSI Sultan Agung Semarang.The type of this research is descriptive qualitative with a cross sectional approach. The research was conducted on May-June 2021 with 2 subjects, namely the insurance officer and the head of the medical record unit. The data were collected by online interviews and analyzed descriptively based on regulations of the Sultan Agung Hospital and the legal aspects of health and then conclusions were drawn.The results showed that the implementation of information release has maintained patient privacy, every release of medical information is followed by permission from the patient/family, release to third parties accompanied by a power of attorney, release of medical information is given by the DPJP doctor. However, the release of medical information has not been involved the director and the regulation on completion time standards has not been implemented optimally. Suggestions from this study is to evaluate the applicable regulations.Keywords: Release of Medical Information, Medical Records, Commercial Insurance